Wokół roku 1420. Początki szkolnictwa renesansowego we Włoszech - Zagrodzka, Alicja (Biuletyn Historii Wychowania, 2021)
Paul F. Grendler suggested the year of 1420 as a symbolic date marking the dawn of Renaissance humanist teaching in the Latin education system. In 1420, the commune of Verona employed Guarino Guarini da Verona (1374–1460) to teach on the basis of Cicero’s letters and speeches. The anniversary has posed an opportunity to challenge a stereotype of two epochs: the Middle Ages and Renaissance, perpetuated in contemporary narration. I have presented my own image of these epochs, synthetic and simplified, yet based on historical facts. The synthetic approach to the similarities and differences between the Middle Ages and Renaissance, suggested here, is coherent with the changes which took place at the dawn of Italian Renaissance education (presented in the second part of the article). I have found out that this development was possible owing to personal contacts among humanists and their familiarity with inspiring texts. I have also discovered that before 1420, before Renaissance humanist education was introduced to public city schools, it had left its mark on self-education, informal relations, private city schools and urban home schooling. Only then did studia humanitatis became attractive to Italian communes and started to employ teachers knowledgeable about the new curriculum. The differences between the Renaissance and medieval education models in Italian public city schools include primarily the means at hand (i.e. the curriculum, the obligatory reading and partly the teaching organisation). They did not pertain to the major goals set by the then teachers (i.e. providing children and adolescents with knowledge and skills that they found useful in adult life, coupled with moral teaching and developing their habits). In my opinion, the Renaissance education model is continuation of the medieval model rather than its opposition because these two models complement each other harmoniously.